Adapted Sport: A Bibliometric Analysis - Jofre Pisà-Canyelles; Jorge Pérez-Gómez; Antonio Castillo-Paredes; Angel Denche-Zamorano; Raquel Pastor-Cisneros; Jesús Siquier-Coll; Sabina Barrios-Fernández; María Mendoza-Muñoz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Adapted sports (AS) allows the physical activity level to increase in groups such as people with disabilities, pregnant women, children and older people. AS modifies conventional sports' formal structure to make them accessible. This study aimed to analyse the trend followed by the annual publications on this topic and identify the most productive and cited authors, journals, and countries with the highest number of publications, the most cited documents and the most used keywords. The search was conducted in the Web of Science (WoS) and traditional bibliometric laws were applied. A total of 398 documents were identified. The annual publications followed an exponential growth trend (R2=89.5%). "Influence of Adapted Sport on Quality of Life: Perceptions of Athletes with Cerebral Palsy" was the most cited document. The categories of most interest to researchers were Sports Science and Rehabilitation. The journal with the higher number of publications was Retos-Nuevas Tendencias en Educación Física, Deportes y Recreación. The USA had the highest number of published documents (122 documents) and citations (973), leading extensive research networks worldwide. A total of 1270 authors have published on this topic, using "adapted sport", "adaptive sport", "disability, and "physical activity" as the most used keywords. Makhov (12 documents) was the most prolific co-author, and Lundberg was the most cited.